Keanekaragaman Jenis Makroalga di Perairan Pulau Nangka Kabupaten Bangka Tengah - Shinta Ahsaniyah; Rahmad Lingga; Henri Henri; Nadila Puspita Sari; Putri Ayu Indah Suryani; Inayah Assyifa (EKOTONIA: Jurnal Penelitian Biologi, Botani, Zoologi, dan Mikrobiologi, 2021)
Macroalgae is one of the main components making up coastal ecosystems that contribute to maintain the marine ecosystem. This research aims to study macroalgae the diversity and the environmental factors that affect the presence of macroalgae in the coastal area of Nangka Island. Samples were obtained from 2 spots arround the coastal area of Nangka island using exploration survey methods. Identification was conducted in Botanical laboratory of Biology Departement, Universitas Bangka Belitung. Water and soil temperature were measured as enviromental factor parameters. The diversity was determined base on three different indexs; the diversity, species evenness and species dominant. The study succesfully identified 4 different species of macroalgae from coastal are of Nangka island including Padina australis, Ulva linneaus, Kappaphycus alvarezii, and Acantophora spicifera. The results of the calculation of the diversity, evenness, and species dominant index shown that the abundance of macroalgae on Nangka Island can be categorized as low. Enviromental temperature for growth was suspected as the factor that affect the diversity of macroalgae arround the coastal area of Nangka island